2022
DOI: 10.1186/s40478-022-01377-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of NF2 alteration in grade I meningiomas revisited; prognostic impact integrated with extent of resection, tumour location, and Ki-67 index

Abstract: NF2 alteration is the most commonly–found genetic abnormality in meningiomas and is known to initiate events for aggressive-type meningiomas. Whereas the prognosis of meningiomas differs depending on their epigenomic/transcriptomic profile, the effect of NF2 alteration on the prognosis of benign meningiomas is not fully elucidated. This study aimed to probe the importance of NF2 alteration in prognosis of WHO grade I meningiomas. A long-term retrospective follow-up (5.3 ± 4.5 years) study involving 281 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…6,33 One recent study found that among grade I NF2-mutated and non-NF2-mutated meningiomas that underwent STR, infratentorial tumors had significantly better PFS than supratentorial ones. 34 Indeed, we have demonstrated similar findings. Furthermore, among skull base meningiomas in general, decreased EOR does not seem to correlate with recurrence, 6 and the risk of recurrence plateaus approximately 8 years after surgery, unlike in non-skull base tumors in which the risk continues to increase with time.…”
Section: Discussionsupporting
confidence: 82%
“…6,33 One recent study found that among grade I NF2-mutated and non-NF2-mutated meningiomas that underwent STR, infratentorial tumors had significantly better PFS than supratentorial ones. 34 Indeed, we have demonstrated similar findings. Furthermore, among skull base meningiomas in general, decreased EOR does not seem to correlate with recurrence, 6 and the risk of recurrence plateaus approximately 8 years after surgery, unlike in non-skull base tumors in which the risk continues to increase with time.…”
Section: Discussionsupporting
confidence: 82%
“…A meta-analysis investigating data from 677 patients revealed that TERT alterations predicted progression-free survival independent of the WHO grades in meningiomas [ 61 ]. Furthermore, loss of the NF2 suppressor gene at chromosome 22 has been demonstrated in a higher percentage (50–60%) of meningiomas, and supratentorial meningiomas with NF2 alterations had higher MIB-1 indices and a shorter time to tumor progression [ 62 , 63 ]. Those emerging molecular markers and their association with shape will be of importance in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor location was categorized as supratentorial or infratentorial, as described previously. 17 All manipulations performed in the present study were in accordance with the 1964 Declaration of Helsinki and its later amendments. The study was approved by the local ethics committee at Hokkaido University Hospital.…”
Section: Patient Populationmentioning
confidence: 99%